Can tax planning improve delay in financial reports? - Pronosokodewo, Baniady Gennody; Susanti, Wahyu Febri Eka (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2023)
The research objective is to see the effect of tax avoidance on delays in financial reports with public accounting firm size and company size as control variables. The population in this research is companies suspended by OJK from 2019 to 2021. The research used purposive sampling, and the data used was panel project data. The research sample is 90 companies listed on the IDX in 2019-2021. The analytical method uses descriptive statistical analysis and inner model analysis to test the hypotheses processed with SmartPLS 4.0. The results show that tax avoidance has a negative effect on delays in financial reports.